Japan : Staff Report for the 1999 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 1999)
This 1999 Article IV Consultation highlights that Japanese growth has been lackluster throughout most of the 1990s. Since the asset price bubble burst in 1991, the economy has grown at an average of 1 percent per year, in striking contrast to the rapid growth achieved in previous decades. A series of fiscal stimulus packages raised the structural general government deficit by more than 5 percentage points of GDP between FY1991 and FY1998, while monetary policy has progressively eased.